Childhood gambling experiences and adult problem gambling - Diarmaid Ó Ceallaigh; Shane Timmons; Deirdre Robertson; Pete Lunn (The Economic and Social Research Institute (ESRI), 2024)
Many countries are strengthening their regulation of the gambling industry. Measures to protect children from exposure to gambling are often an important component of regulation, as childhood exposure to gambling is thought to lead to problem gambling (PG) in adulthood. We report a preregistered analysis of survey data from a nationally representative sample of adults in Ireland (N = 1,663). Almost two-in-three adults (64%) report having gambled before turning 18 and doing so is associated with an almost doubling of the risk of later-life PG. Having a parent who gambled and having parents with more positive attitudes towards gambling are also associated with increased risk of PG. Those who had a parent that gambled a lot are almost twice as likely to have PG. However, the relationship between parental behaviour and PG is weaker among younger age groups. Our findings support child-focused regulatory measures to restrict access and exposure to gambling for children.
Keywords: 330